2022
DOI: 10.1073/pnas.2201541119
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of antigen receptor repertoire disruption across adaptive immune compartments in COVID-19

Abstract: Whereas pathogen-specific T and B cells are a primary focus of interest during infectious disease, we have used COVID-19 to ask whether their emergence comes at a cost of broader B cell and T cell repertoire disruption. We applied a genomic DNA-based approach to concurrently study the immunoglobulin-heavy (IGH) and T cell receptor (TCR) β and δ chain loci of 95 individuals. Our approach detected anticipated repertoire focusing for the IGH repertoire, including expansions of clusters of related sequences tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…15 While no differences in Vd1 + T cells have been identified, a recent study showed that TCRd1 + (TRDV1) CDR3 sequences showed evidence of clonal focusing in COVID-19 patients aged > 50 years. 16 cd T cell subsets have been implicated in controlling other viral infections such as CMV and severe acute respiratory syndrome (SARS). In CMV, Vd1 + T cells expanded rapidly and undergo cd TCR clonotype expansion upon infection in both stem cell 17 and kidney [18][19][20][21] transplantation settings and have been implicated in the resolution of CMV infection.…”
Section: Introductionmentioning
confidence: 99%
“…15 While no differences in Vd1 + T cells have been identified, a recent study showed that TCRd1 + (TRDV1) CDR3 sequences showed evidence of clonal focusing in COVID-19 patients aged > 50 years. 16 cd T cell subsets have been implicated in controlling other viral infections such as CMV and severe acute respiratory syndrome (SARS). In CMV, Vd1 + T cells expanded rapidly and undergo cd TCR clonotype expansion upon infection in both stem cell 17 and kidney [18][19][20][21] transplantation settings and have been implicated in the resolution of CMV infection.…”
Section: Introductionmentioning
confidence: 99%
“…We collected immune repertoire sequencing data for a total of 285 individuals, comprising 152 healthy individuals and 133 subjects with disease (79 COVID-19 patients and 54 autoimmune hepatitis patients) from 5 independent datasets ( 15 , 16 , 18 20 ). All studies from which the sequence information was gathered performed targeted immune receptor sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted replication and validation analyses on a separate study with 43 healthy controls and 32 COVID-19 patients ( 20 ). In this study, genomic DNA from peripheral blood mononuclear cells were isolated to generate immune receptor libraries using the immunoPETE protocol from Roche Sequencing Solutions, providing sequence information for an average of 22,834 T cell clonotypes and 9,141 B cell clonotypes per individual.…”
Section: Methodsmentioning
confidence: 99%
“…With regard to cardiovascular medicine, it is desirable to know specific genetic risk factors for the development of myocarditis during COVID-19 or upon vaccination [112,[165][166][167][168][169][170][226][227][228][229][230][231][232], or for development of long COVID syndromes [191,[233][234][235][236][237][238][239]. Fortunately, SARS-CoV-2 is rather rarely causing severe myocarditis or cardiomyopathies [165][166][167][168][169][170].…”
Section: Cardiovascular Immunobiology Of Covid-19 and Long Covid Synd...mentioning
confidence: 99%